Blue Finance: Is this supporting SDG 14 Financing Gap - Wanta, Derry; Khomsiyah, Khomsiyah; Gunawan, Juniati (IJOSMAS, 2023)
The stagnation of the worlds traditional land-based economies and the depletion of natural resources on land has fuelled interest in the development of the marine economy. Indonesia is the largest archipelagic country in the world, with 70% of its area covered by ocean. Its potential to establish a Blue Economy as a government revenue source can help achieve the targets of SDG 14. Indonesia Minister of Finance and Ministry of National Planning reiterated that the President had asked government officials to look into potential aspects of the maritime sector so that the Blue Economy becomes an important aspect. To establish Blue Economy, need effort to develop Blue Finance and the governance. The following question will be addressed in the paper: How Blue Finance in Indonesia support the achievement of SDG 14?. The primary method employed in this research is qualitative and involves a desk study and interviews with relevant respondents. The results reveal that currently, Government of Indonesia (GoI) focus to complete 14.4.1 (proportion of fish stocks within biologically sustainable levels) and 14.5.1 (protected area coverage in relation to marine areas). There are no figures available regarding the ideal financial needs to achieve SDG 14 in Indonesia until 2030 until yet, however process in on going. There is an essential collaborate with all potential stakeholders to speed up the establishment of Blue Economy in Indonesia in order to achieve SDG 14 target. Furthermore, the Blue Finance Advisory Committee in Government should establish to synergize and coordinate all stakeholder